Incidente de desconsideração da personalidade jurídica: aplicação nas execuções fiscais e nos casos de responsabilização de terceiros – uma análise pragmática - Chilo, Fabio Augusto (2025)
This work addresses the applicability or not of the incident of disregard of legal personality (IDPJ), inserted into the civil procedure code by Law No. 13,015/2015, in tax enforcement processes. We carry out an initial analysis regarding passive subjection and responsibility, exploring whether the incident itself is really something new in the legal system or whether there was already provision for the application of this institute – or some other mechanism independent of the name attributed to it – either in the Civil Procedure Code as well as in other existing legal and constitutional provisions. Furthermore, in addition to studying in detail the compatibility or otherwise of the incident of disregarding the legal personality with tax foreclosures, we explored the extent of its application, that is, once the application of the incident was admitted, this important tool could be admitted for the partners to discuss your responsibility or also so that other third parties could make use of it? We evaluate and criticize whether cases of business succession, for example, should be subject to a prior adversarial process with the possibility of an incident involving disregard of legal personality or whether, in these cases, the succession is direct, with the incident being an exclusive remedy for the partners and administrators. From the perspective of pragmatism, we analyze whether the Incident of Disregard of Legal Personality achieves the defense of contradictory and broad defense and whether or not any limitations of its application interfere with its purpose. Finally, we make an overview of current jurisprudence, both from higher and regional courts, to help with the conclusion and our position on the topic brought up, which is due to the breadth of use of this important tool